2009
DOI: 10.1104/pp.109.137505
|View full text |Cite
|
Sign up to set email alerts
|

The Cytokinin Type-B Response Regulator PtRR13 Is a Negative Regulator of Adventitious Root Development inPopulus       

Abstract: Adventitious root formation at the base of plant cuttings is an innate de novo organogenesis process that allows massive vegetative propagation of many economically and ecologically important species. The early molecular events following shoot excision are not well understood. Using whole-genome microarrays, we detected significant transcriptome remodeling during 48 h following shoot removal in Populus tremula 3 Populus alba softwood cuttings in the absence of exogenous auxin, with 27% and 36% of the gene mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
133
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(144 citation statements)
references
References 80 publications
6
133
0
Order By: Relevance
“…(De Klerk and Hanecakova, 2008;Kilkenny et al, 2012), but at low auxin levels, ethylene promoted adventitious rooting in mung bean (De Klerk and Hanecakova, 2008). Ethylene is known to interact with both auxin (R uzicka et al, 2007;Lewis et al, 2011) and cytokinin (Bollmark and Eliasson, 1990;Ramírez-Carvajal et al, 2009), but the precise nature of this interaction in cutting propagation requires further study.…”
Section: Adventitious Root Initiationmentioning
confidence: 99%
“…(De Klerk and Hanecakova, 2008;Kilkenny et al, 2012), but at low auxin levels, ethylene promoted adventitious rooting in mung bean (De Klerk and Hanecakova, 2008). Ethylene is known to interact with both auxin (R uzicka et al, 2007;Lewis et al, 2011) and cytokinin (Bollmark and Eliasson, 1990;Ramírez-Carvajal et al, 2009), but the precise nature of this interaction in cutting propagation requires further study.…”
Section: Adventitious Root Initiationmentioning
confidence: 99%
“…Transgenic lines expressing an active form of the Populus type-B cytokinin response regulator PtRR13 (ΔDDKPtRR13) have a delayed rooting phenotype and cause misregulation of CONTINUOUS VASCULAR RING1, a negative regulator of vascularization. Inappropriate cytokinin action via ΔDDKPtRR13 expression appeared to disrupt adventitious root develop-ment 24 h after shoot excision, when root founder cells are hypothesized to be sensitive to the negative effects of cytokinin (Ramirez-Carvajal et al, 2009). …”
Section: Genes Asociated With the Adventitious Root Formationmentioning
confidence: 99%
“…Our knowledge of adventitious rooting in trees is limited. It has been shown that the expression of SCARECROWlike genes is induced during rooting (Sánchez et al, 2007), whereas the expression of a cytokinin type B response regulator (PtRR13) is negatively modulated during the early steps of adventitious root formation in poplar (Populus trichocarpa) stem cuttings (Ramírez-Carvajal et al, 2009). Moreover, the PtRR13-dependent pathway interfered with auxin transport and inhibited the transcription of two APETALA2/ETHYLENE RESPONSE FACTOR (AP2/ERF) transcription factor genes.…”
mentioning
confidence: 99%